Penatalaksanaan Fisioterapi Pada Kasus Post Open Reduction Internal Fixation (Orif) Fracture 1/3 Distal Radius Sinistra di RSUD Dr. Moewardi Surakarta - Asmarani, Aulia Atika; , Wahyuni, SKM., M.Kes (2017)
Background: Radius fracture is the breakdown of bone continuity that occurs in the radius bone. Fracture of the radius is divided into 3 fractions of the proxsimal, medial and distal portions. Problematics Physiotherapy can be found in the case of tenderness and motion pain at 1/3 distal radius, spasm in the muscles of the lower arm of the sinisra, decreased flexor muscle strength, extensor, radial deviation and ulnar deviation 1/3 distal radius, limitations of motion scope Joints (LGS) 1/3 distal radius, and decreased functional activity. Methodes: Physiotherapy methods used in the case were with Infrared modalities and exercise therapy, and evaluation by pain measurement method (VDS), muscle strength (MMT), and measurement of LGS with Goneometer. Objective: To find out the benefits of Infrared modal modalities and exercise therapy in reducing pain, reduce muscle spasms, increase muscle strength, improve LGS. Results: After 6 treatments, the result of decreased tenderness and motion pain, reduced muscle spasms and increased muscle strength, increased LGS. Conclusions: In such cases, giving Infrared modalities and exercise therapy can reduce pain, reduce muscle spasms, increase muscle strength, and improve LGS.